Quantification of browning kinetics and colour change for quince (Cydonia oblonga Mill.) exposed to atmospheric conditions - Guiné, Raquel (2015)
Because quince is a fruit that shows a very strong tendency for developing an intense browning when exposed to air, even though for short periods of time, the aim of this work was to evaluate the kinetics of colour change for quince exposed to atmospheric air at ambient temperature over a period of 2 hours. The quince was cut into slices that were left exposed to air, and colour measurements were done right after cutting and every 5 min, using a tristimulus colorimeter measuring the CIELab coordinates, L*, a* and b*. The results confirmed that quince suffers a high degree of browning, with total colour difference increasing strongly from 0 to 30 and browning index increasing from 50 to near 140. Furthermore, the major colour changes occurred during the first 30 min of exposure. Different models were tested to fit experimental data and the results showed that the most commonly used models, zero-order and first-order kinetics were totally inadequate in the present case, while the less cited models revealed to be very good at describing the kinetics of colour change for quince: logistic, modified Maskan and exponential rise.